Geomorphological effects of tropical cyclones in Costa Rica, Central America - Quesada Román, Adolfo (2024)
Tropical cyclones have provoked intense devastation over the last decades, and societal drivers such as unplanned urbanization and the lack of flood risk assess-ment have worsened the problem. Landslides and floods constitute a frequent hazard linked to tropical cyclones. This is not the exception in Costa Rica, where hydrom-eteorological disasters sum more than 90% of the total. Different climatic change scenarios indicate that a large number and more strong tropical cyclones will affect the North Atlantic Ocean Basin, where Central America and the Caribbean Sea lie. This study comprises different methodologies to understand the geomorphic effects of tropical cyclones in Costa Rica. This chapter presents geomorphological, hydro-logical, dendrochronological, and risk assessment approaches that aim to reduce the human and economic impact of tropical cyclones. Finally, the chapter calls for applying geomorphic assessments to elucidate the endogenic and exogenic processes controlling the effects of tropical cyclones in low latitudes.